Int-Soft (Generalized) Bi-Ideals of Semigroups - Young Bae Jun; Seok-Zun Song (The Scientific World Journal)
The notions of int-soft semigroups and int-soft left (resp., right) ideals in semigroups are studied in the paper by Song et al. (2014). In this paper, further properties and characterizations of int-soft left (right) ideals are studied, and the notion of int-soft (generalized) bi-ideals is introduced. Relations between int-soft generalized bi-ideals and int-soft semigroups are discussed, and characterizations of (int-soft) generalized bi-ideals and int-soft bi-ideals are considered. Given a soft set (α;S) over U, int-soft (generalized) bi-ideals generated by (α;S) are established.